Preoperative Pulmonary Function test and Pulse Oximetry among Patients Recovered from COVID-19 Who Were Candidates for Elective Surgery - Nilofar Massoudi; Mohammad Javad Nasiri; Navid Nooraei; Malihe Abniki (Novelty in Biomedicine, 2024)
Background: This descriptive study aimed to assess preoperative pulmonary function test (PFT) results and pulse oximetry readings in patients recovered from COVID-19 who were candidates for elective surgery.